2020
DOI: 10.21475/ajcs.20.14.04.p1528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light, agar, activated charcoal, and culture medium on the germination and early development of Dendrobium seedlings

Abstract: The objectives of this study were to determine the optimal light conditions, agar concentration, and quantity of activated charcoal in asymbiotic media to improve the in vitro seed germination rate and early seedling development of the epiphytic orchids Dendrobium nobile Lindl. and Dendrobium phalaenopsis Fitzg. Two independent experiments with complete randomized designs were conducted. (1) Treatments were arranged in a split-plot scheme. Seeds in each sub-plot were exposed to one of four light conditions (da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…Therefore, 4.5 g/L of agar is seen to be optimum for the growth of plantlets. Other than that, Sorgato et al (2020) reported that no presence of charcoal and concentration of agar more than 4.0 g/L resulted in better growth of protocorm-like bodies similar to the indings in Figure 3 . Therefore, not only 4.5 g/L of agar is suitable for plantlets growth but also is optimal for PLBs.…”
Section: Resultssupporting
confidence: 60%
“…Therefore, 4.5 g/L of agar is seen to be optimum for the growth of plantlets. Other than that, Sorgato et al (2020) reported that no presence of charcoal and concentration of agar more than 4.0 g/L resulted in better growth of protocorm-like bodies similar to the indings in Figure 3 . Therefore, not only 4.5 g/L of agar is suitable for plantlets growth but also is optimal for PLBs.…”
Section: Resultssupporting
confidence: 60%
“…Furthermore, the 3 g/L -1 activated charcoal concentration produced the highest germination percentage due to the limited light provided to the medium. According to Sorgato et al (2020), germination was accelerated under light limitation on the medium. The development stages of C. rochussenii de Vriese with four basal media are visualized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The germination of seeds via in-vitro propagation is still low with a range of 30-45%, meanwhile, the germination percentage is influenced by the presence of light in the medium (Sorgato et al, 2020). Besides, the various types of orchids respond differently to the percentage of light in the media, hence, it is necessary to add a light-reducing ingredient in the form of activated charcoal.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors may influence the germination, growth and development of plants grown in vitro. These factors include the culture medium, sealing system and light condition used for cultivation (Silva et al 2015, Silva et al 2016, Sorgato et al 2020. Some adjustments are still necessary in the culture medium formulation for each orchid species, especially native ones.…”
Section: Special Supplement: Cerrado [Brazilian Savanna]mentioning
confidence: 99%